Ethnobotany as an integral of indigenous cultural heritage: case studies on orang jakun and semelai of Tasik Chini and Tasik Bera, Pahang, Malaysia - Mohd. Zain, Zainul Hakim (2007)
Ethnobotany is the study of a region's plants and their practical uses through the traditional knowledge of a local culture and people.